Integral assessment of antioxidant status of fruit vegetables - Прісс, Олеся Петрівна; Малкіна, Віра Михайлівна; Калитка, Валентина Василівна (Eastern-European Journal of Enterprise Technologies, 2014)
The integral assessment of the antioxidant status of fruited vegetables can be a key when choosing a product suitable for storage. Making the integrated assessment of the antioxidant system of fruited vegetables taking into account the differences in units of measuring the system components is a difficult task. For solving complex multicriteria informal problems, the hierarchy analysis method was used. The method for determining the generalized integral assessment of the antioxidant status of fruited vegetables based on the hierarchy analysis method was proposed. The components of the antioxidant system of protecting fruited vegetables tissues were ranked. The integral assessment showed that among the studied fruits pepper had the highest antioxidant status (ІАО=0.43), squash had the minimum (ІАО=0.12). Due to a powerful system of high antioxidants, cucumbers had higher integrated assessment (ІАО = 0.25) than tomatoes (ІАО =0.20). Low-molecular antioxidants make the main contribution to the antioxidant status of solanaceous vegetables. Enzymatic antioxidants play a leading role in antioxidant protection of tissues in pumpkin vegetables.